Five-coordinate copper(II) complexes: Crystal structures, spectroscopic properties and new extended structural pathways of [Cu(chelate)2X]Y, where chelate = dpyam, phen and bipy; X = pseudohalide ligands - Sujittra Youngme (2018)
The crystal structures of four distortion isomers of the [Cu(chelate)2 X]+cation, where chelate = 2,2-bipyridine (bipy), 1,10-phenanthroline (phen) and di-2-pyridylamine (dpyam), X = a pseudohalide ligand (NCO, NCS, N3 and C2N3), have been compared by scatterplot analysis with 25 [Cu(chelate)2 X]Y complexes of known crystal structure. The four new complexes [Cu(phen)2NCO]Br (1), [Cu(phen)2N3]BPh4·H2O (2), [Cu(dpyam)2(N3)]NO3·H2O (3) and [Cu(dpyam)2(N3)]ClO4 (4) involve a near regular square-based pyramidal stereochemistry (RSBP). The structures of complexes (1) and (2) are of the rare cases found for the phen analogue. Scatterplots of the 29 cation distortion isomers of the [Cu(chelate)2 X]Y series of complexes suggest that most of the 29 complexes lie on a common structural pathway, involving a mixture of the symmetric, C 2, and the asymmetric, non-C 2, in-plane modes of vibration of the CuN4N′ chromophore. Some datapoints are found to lie on extended routes The resulting structural pathways are consistent with the direct observation of the effect of the modes of vibration on the stereochemistries of the complexes. A comparison of the trends in the 29 datasets suggests a size effect of the phen, bipy and dpyam ligands. © 2008 International Union of Crystallography.